Interconnection Inverter Control System of PMSG Wind Power Generation - Saravut Reangkittakarn; Sirichai Tammaruckwattana (My University, 2017)
This paper presents the experimental results of the operation of the system interconnection inverter control side for wind power generation system (WPGS) using PMSG. The diode bridge rectifier converter methods are utilized as converters for the WPGS. The experimental results are obtained by the test bench using the wind turbine emulator. The wind turbine emulator are reproduced the behaviours of windmill by the servo motor drives. The servo motor is calculated from windmill wing profile, the wind velocity and windmill rotational speed. The WPGS using PMSG employs the vector control system to control the torque and speed of PMSG and the active power and reactive power are controlled and generated power is sent to the grid-connected power generation while controlling the DC link voltage in the inverter side.
Keywords: Windmill; Rectifier (neural networks); Test bench; Wind Turbine Control Systems